(untitled) (Jurnal Simki Economic, 2025)
Maintaining wise financial patterns among excessive spending habits can support financial health. Financial health is very important so that basic needs can be met properly through proper budget management. Understanding financial management is considered very important lately for individuals in managing income, monitoring expenses, investing, and planning finances for the future so that it affects their financial and social well-being. This study aims to gain an understanding of the influence of parental income, financial literacy, and locus of control on the management of financial behavior of students in Jember City. Data testing uses multiple linear regression. The sample taken consists of 180 students in Jember City. The sample was taken using probability sampling through the stratified random sampling method. The results of the study found that parental income, financial literacy, and locus of control positively and significantly affect financial management behavior, both individually and together.